Study of Lipid Profile in Shift Workers - Rahman, Md Abedur; Amin, Md Ruhul; Begum, Momotaj; Khatun, Firoza; Islam, Montasir; Akther, Dilruba (Journal of Bangladesh Society of Physiologist, 2008)
Background: The present study was undertaken to evaluate the changes of serum lipid profile in apparently healthy shift workers and non shift workers to identify the possible high risk factors for developing atherosclerotic changes. Methods: Serum Total Cholesterol, Triglyceride, HDL-Cholesterol and LDL-Cholesterol levels were estimated and blood pressure was measured in apparently healthy adult shift worker and non shift worker participants. Total 60 subjects age ranged from 20-50 years were selected, of whom 30 were shift workers (Study) for at least one year and 30 were non shift workers (control). Height, weight and resting blood pressure of all the subjects were recorded before collection of blood. Blood samples were collected after over night fasting for estimation of serum lipid and lipoprotein levels and were measured by standard laboratory technique. Data were analyzed by unpaired ‘t' test. Results: The mean serum Total Cholesterol and LDL-Cholesterol levels were significantly higher in shift workers compared to those of non shift workers. Again mean serum Triglyceride and HDL-Cholesterol levels in the shift workers did not differ significantly from that of non shift workers. These changes may be related to internal desynchronization due to disruption of circadian rhythm. Conclusion: The changes in serum lipid and lipoprotein levels with the exception of HDL-Cholesterol and Triglyceride in the subjects engaged in shift work may put them at increased risk for coronary artery disease. Keywords: Circadian Rhythm; Lipid Profile; Shift-work DOI:10.3329/jbsp.v2i0.982 J Bangladesh Soc Physiol. 2007 Dec;(2): 34-37.